Forms of Cooperation Between the Polish Security Service and the State Security Committee of the Soviet Union on the Ukrainian Issue (1956–1989) - Аркадіуш Слабиґ (Історико-політичні проблеми сучасного світу)
Due to its international aspect, the Ukrainian issue became the subject of cooperation between the Security Service (SB) of the Ministry of Internal Affairs (MSW) of the Polish People’s Republic (PRL) and the State Security Committee (KGB) of the Soviet Union. Cooperation involved counterintelligence services, departments to destroy the political opposition and the so-called ideological and political subversion, and departments controlling religious life. In the first half of the 1970s, the Management of Special Departments of the KGB at the Northern Group of Soviet Forces (in Poland) also took part in special operations against Ukrainians. The design of joint operational activities as well as the exchange of views and information was facilitated by working meetings organized in capital cities and at border crossings. One of the first documented meetings on the Ukrainian question after the period of the political “thaw” was held in May 1958, and the last, most likely at the turn of 1988 and 1989, in Minsk, Belarus. The basic areas of cooperation include: surveillance and disintegration of Ukrainian emigration (mainly rival factions of the nationalist movement), prosecuting Ukrainian war criminals and collaborators who avoided responsibility, surveillance of Ukrainian citizens of the Polish People’s Republic suspected of carrying out “nationalist activities”, signaling threats to the security of the state generated by Ukrainian population as well as standard completion and verification of archival materials concerning the controlled persons. The operational activities of the secret services of Poland and the Soviet Union required the involvement of so-called personal information sources, i.e. secret collaborators. They were Polish and Soviet citizens of Ukrainian nationality, with numerous relatives and friends in Poland, the Soviet Union and Western countries. This allowed them to cross state borders, despite restrictive passport regulations. The Security Service recruited them to cooperate by threatening with imprisonment, embarrassment, and dismissal from work or studies. Support was also offered in finding a job or a flat, and it was also possible to renew contacts with relatives abroad. These were effective tools for manipulating agents.